Variations of Organic Fertilizer Dose to The Three Varieties of Sweet Sorghum Growth and Yield for Bioethanol - Nurngaini Nurngaini; Rati Riyati (Jurnal Agrivet, 2016)
Field experiments to study "Organic Fertilizer Dose Variations on Three Sweet Sorghum Varieties on Growth and Yield of Sorghum for Ethanol" aimed to 1). Examines the interaction between wide varieties of sweet sorghum with a dose of organic fertilizer. 2). Determine an appropriate dose of organic fertilizer for growing sweet sorghum. 3). Determine the sweet sorghum varieties in response to the dose of organic fertilizer. Research conducted at the Experimental station, Faculty of Agriculture UPN "Veteran" Yogyakarta; using a split plot design with three replications and Research Laboratory, Faculty of Agriculture UPN "Veteran" Yogyakarta. The main plots varieties were: V1: Patir-3, V2: Samurai-2, and V3: Mandau and as subplot were dose of organic fertilizer: D1 = 20 g / plant; D2 = 40 g / plant; and D3 = 60 g / plant. The results showed that: (1) There was interaction between varieties with a dose of organic fertilizer on sorghum stalks weighting parameter. Each of sweet sorghum varieties gave different looks on any given dose of organic fertilizer. (2) Treatment varieties showed real effect on plant height parameter 8 mst, leaf number 8 mst, panicle length, sorghum stalk length, weight of 100 seeds, sorghum stem juice volume and juice sweetness level.Keywords: fertilizers, sweet sorghum varieties, bioethanol